Development Prospects of Ukraine’s Foreign Trade in Agricultural Products in the Context of European Integration and Global Challenges - MATYUSHENKO, Igor Y.; SHTAL, Tatyana V.; PIDDUBNA, Lyudmila I.; PIDDUBNYI, Ivan O.; KVITKA, Yuliia M. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The aim of the article is to determine the status and prospects and to propose recommendations for the development of Ukraine’s foreign trade in agro-industrial products in the context of European integration and global challenges. To achieve this aim, the article investigates the significance of the agrarian complex for Ukraine’s economy, defines the most promising types of agro-industrial products in terms of exports using dynamic statistical, comparative, and correlation-regression analyses, and proposes respective recommendations. Was made a conclusion that Ukraine has a significant share in the world market of grain crops and exceeds the EU indicators for the exports of wheat, barley and maize. The recommendations for improving the positions of Ukraine as an exporter of agro-industrial products suggested in the article include as follows: (1) in order to change raw-based exports of these products, Ukraine has to change the exports towards finished products with a high added value, in particular, organic products that are relatively expensive in the EU countries due to the complexity of their cultivation; (2) technical re-equipment of the agro-industrial complex, which requires considerable capital investments; (3) implementation of the technologies of adaptive soil-protecting farming to prevent degradation of agricultural land; (4) implementation of the modern infrastructure of Ukraine’s agrarian market as proposed by the authors.